Corporate Reporting, Integrated Reporting, and Sustainable Development Goals Disclosures - Dosinta, Nina Febriana; Chen, Ceci Lia; Kusuma, Dewi Agustine (Accounthink : Journal of Accounting and Finance, 2024)
The Sustainable Development Goals (SDGs) were implemented globally around 2016, including a focus on improving corporate welfare. Although previous research has explored factors influencing SDG disclosure in corporate reporting, only a few have investigated the quality of integrated reporting (IR) in Indonesia. Even though it is voluntary, several companies have adopted IR in their corporate reporting. This research investigates the factors influencing SDG disclosure, including the quality of integrated reporting (IR) as a moderation. This research uses twenty banking companies through Moderated Regression Analysis for the 2016-2023 period. The research results show that bank age and financial stability moderated by IR quality positively and significantly affect SDGs. IR quality cannot moderate bank age, board of commissioners supervision, and liquidity risk on SDG disclosure. Companies that operate over a long period maintain legitimacy by fulfilling sustainable development. This research implies that corporate legitimacy in sustainable development will have a greater opportunity to improve corporate welfare. This research implies that even though companies have not reported in the form of IR, companies are trying to meet the quality of IR in corporate reporting.